IMPLEMENTATION OF DESCRIPTION CARDS COOPERATIVE MODEL MAKE A MATCH TO IMPROVE CHILDREN'S INTERPERSONAL AND INTRAPERSONAL INTELLIGENCE. - Desmi Dwi Harsasi; Wachidi Wachidi (DIADIK, 2018)
The porpouse of this research is describe the application of cooperative models make a match aided by picture card to improve interpersonal and intrapersonal intelligence of children in Pembina Selupu Rejang Kindergarten, Rejang Lebong districts. the research method used is collaborative classroom action research, meaning the researchers and teachers learning to improve quality and learning outcomes. The subject of this research is the children in B groups Pembina Selupu Rejang Kindergarten, Rejang Lebong districts which numbered 15 student. Data collection techniques use observation. This research was conducted in three cycles. The results of data analysis showed an increase in interpersonal intelligence, illustrated in the first cycle of 1.74 in the second cycle of 2.6 and in the third cycle there was an increase to 3.54. Likewise, the child intrapersonal intelligence increased, in the first cycle of 1.58 in the second cycle 2.55 and in the third cycle there was an increase to 3.48. The results showed that using cooperative model learning make a match aided by picture cards can improve interpersonal and intrapersonal intelligence in children and very effective, it is shows a significant difference between cycles one, two and three. This learning model is worthy to be used by teachers so that interpersonal and intrapersonal intelligence can increase